IMPROVING STUDENTS' SOCIAL CONCERN THROUGH THE RAMADHAN CHARITY PROGRAM AT ADZKIA PADANG - Meidianas Saputra; Nana Sepriyanti; Martin Kustati (International Journal of Multidisciplinary Reseach, 2026)
The Amaliyah Ramadhan Program is a form of education-based community service oriented towards strengthening students' social character through the habit of sharing, almsgiving, charity, and social action. This study aims to analyze the implementation of the Amaliyah Ramadhan Program in increasing students' social awareness at the Adzkia Foundation in West Sumatra and describe its impact on the beneficiary community. The study used a qualitative descriptive approach with a field study method. Data were collected through observation, documentation, and analysis of the Anshitah Ramadhan Committee (PAR) activity reports for 1447 H/2026 M. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that the program successfully collected alms of Rp191,304,000 and humanitarian donations for Palestine of Rp46,884,000 with the participation of all educational units within the Adzkia Foundation in West Sumatra. The funds were realized in the form of distributing basic food packages and takjil to the community around the school, disaster victims, and community groups in need. This program not only increases student participation in philanthropic activities but also fosters empathy, social solidarity, responsibility, and concern for others through contextual learning experiences. Thus, the Amaliyah Ramadhan Program has proven to be an effective model for strengthening social character education through community service activities based on Islamic values.